Pengaruh pemilihan gigi penyangga terhadap desain cengkeram rangka logam Effect of abutment selection to the clasp design of metal frame - Moh. Dharmautama; Edy Machmud; Asmah Fahmi Rasyid (DiscoverSys Inc., 2012)
Advantages of metal framework partial denture than conventional denture base include power and can be made asthin as possible. But the success is influenced by clasp design. Many things to be considered in positioning theclasp, therefore knowledge of the diagnosis, indications, contraindications, and biomechanical properties of themetal that used to be important in the treatment. This study aimed to determine the retentive strength of akers andback action for the abutment first molar and first premolar and the upper and lower clasp design is mostappropriate for the abutment. Research using 8 samples I (gypsum base with natural teeth) and 8 samples II(gypsum base metal crown) maxillary and mandibulary first premolar and first molar with a depth of 0.25 mmundercut. Sample II soaked in artificial saliva, surveyed and was prepared for a rest seat. Akers and back actionclasp were inserted on a metal crown and measured their retentive strength with Instron UTM. The results obtainedindicate the highest retentive strength metal abutment crown molar and premolar with Akers compared to backaction. Highest retentive strength on metal molar abutment crowns with the Akers and upper premolars with metalcrowns back action. There are significant differences between the groups retentive strenth of clasp design. It wasconcluded that best retentive force on the upper molars with akers and upper premolars with Akers.